PROBLEMATIKA DUNIA KEPENGARANGAN SASTRA JAWA PERIODE 1980—1997: SEBUAH STUDI KASUS (Problems of Javanese Literary Authorship World in the Period of 1980—1997: A Case Study) - Priyo Prabowo, Dhanu (METASASTRA: Jurnal Penelitian Sastra, 2013)
Dunia kepengarangan sastra Jawa periode 1980—1997 ditopang oleh media berbahasa Jawa (koran dan majalah). Kehadiran institusi itu ternyata mampu memberikan kontribusi yang sangat luas terhadap sistem kesastraan Jawa. Kenyataan ini menunjukkan bahwa institusi-institusi itu telah mampu menggeser peranan penerbit buku. Di tengah situasi seperti itu, pengarang Jawa menggunakan nama samaran perempuan untuk memertahankan eksistensinya (ekonomis dan popularitas). Usaha tersebut ternyata dapat memperteguh sikap para pengarang sastra Jawa dalam memertahankan sastra Jawa, walaupun keadaan ekonomi para pengarang sastra Jawa sangat kecil jumlahnya jika dibandingkan dengan pengarang sastra Indonesia. Sastra Jawa sebagai sastra daerah di Indonesia tetap dapat dipertahankan ekistensi oleh para para pengarang baru dan pengarang lama. Penelitian ini menggunakan teori makro sastra dari Ronald Tanaka. Dengan teori itu, penelitian ini dapat mengungkapkan dunia kepengarangan sastra Jawa pada periode 1980—1997. Adapun metode sosiologis dalam penelitian dipergunakan untuk memahami secara komprehensif persoalan di dalam dunia sastra Jawa periode 1980—1997.Abstract:Javanese literary authorship world in the period of 1980-1997  supported by Javanese media (newspaper and magazine). The presence of the instituation was able to give a broader contribution to Javanese literary system. The fact showed that the institutions had been able to shift the role of book’s publisher. In the midst of such a situation, the Javanese authors wrote under pseudonyms to maintain their existence (economic and popularity). The effort  was able to rein- force the literary Javanese  authors’ attitude in preserving the Javanese literature despite the economic condition in this period that made their payment for their works very small when com- pared to Indonesian literary authors’ payment. The existence of Javanese literature as regional literary works  in Indonesia can still be maintained by new  and  old authors. The present study applies the  Ronald Tanaka’s literary macro theory. By using the theory, the research tries to  reveal the world of Javanese literary authorship  in the period of 1980—1997.  The sociological method of the research is used to understand problems comprehensively in Javanese literary world in the period of 1980—1997.